Mother-to-child transmission of HIV in the Southern Region of Santa Catarina, from 2005 to 2015: analysis of risk factors to seroconversion in newborns - Karen Waleska Kniphoff de Oliveira; Suzana Kniphoff de Oliveira; Ana Beatriz Sanches Barranco; Tamara Hoffmann; Camila Soares Duarte; Rayane Felippe Nazário; Chaiana Esmeraldino Mendes Marcon; Fabiana Schuelter-Trevisol (Revista Brasileira de Saúde Materno Infantil)
Abstract Objectives: to analyze both frequency and risk factors for seroconversion among newborns of HIV-positive mothers to HIV. Methods: a cohort study was conducted with children residing in Southern Region of Santa Catarina. Secondary data from the notification files and medical records of newborn's mothers of infected infants were used. The participants were all the newborns from 2005 to 2015 that were exposed to HIV through vertical transmission and attended a municipal health care center. Results: there were 104 cases of infant exposure to HIV. Seroconversion was confirmed in three cases, two of them died of AIDS during the study period. Breastfeeding (PR= 32.7; CI95%= 10.7-99.5; p= 0.002) and non-use of antiretroviral drugs during pregnancy (PR=18.2; CI95%= 2.0-163.0; p= 0.008) were risk factors for HIV seroconversion. Conclusions: seroconversion rates among neonates in Southern Region of Santa Catarina were similar to the national average. Seroconversion was associated with non-use of antiretroviral therapy during pregnancy and breastfeeding.